Caffeine and resistance exercise: the effects of two caffeine doses and the influence of individual perception of caffeine - Doederlein Polito, M.; Grandolfi, K.; Brito de Souza, D. (European Journal of Sport Science, 2019)
Although caffeine is a widely used ergogenic resource, some information regarding its effects on resistance exercises is still lacking. The objective of the present study was to verify the acute effect of the ingestion of two different doses of caffeine on performance during a session of resistance exercises and to analyze the perception of the subjects in relation to the intake of caffeine. Following a double-blind, randomised, cross-over, controlled, and non-placebo design, 14 trained and healthy men (24.7?±?6.8 years; 79.8?±?9.8 kg; 177.3?±?8.5 cm) performed a training session in chest-press, shoulder-press, and biceps curl exercises (3 sets until exhaustion; 70% 1RM; 3 min rest interval; 2 s for each concentric and eccentric phase) on three non-consecutive days after ingestion of 3 mg.kg-1 caffeine (CAF3), 6 mg.kg-1 caffeine (CAF6), or no substance (CON). Subjects were informed that one of the caffeine doses would be placebo. The total number of repetitions performed in CON (93.6?±?22.4) was significantly lower than in CAF3 (108.0?±?19.9, P?=?0.02) and in CAF6 (109.3?±?19.8, P?=?0.03) and there were no differences between caffeine doses. Eight subjects noticed that caffeine was in CAF3 and six in CAF6 and there were no differences in the number of repetitions between sessions in which the subjects perceived and did not perceive caffeine. In conclusion, caffeine doses of 3 or 6 mg.kg-1 similarly increased performance in resistance upper limb exercises, independent of the subject's perception of substance ingestion.